2021
DOI: 10.3390/ijerph18052747
|View full text |Cite
|
Sign up to set email alerts
|

Lead Emissions and Population Vulnerability in the Detroit Metropolitan Area, 2006–2013: Impact of Pollution, Housing Age and Neighborhood Racial Isolation and Poverty on Blood Lead in Children

Abstract: This research investigates the relationships between airborne and depositional industrial lead emission concentrations modeled using Environmental Protection Agency’s (EPA’s) American Meteorological Society/Environmental Protection Agency Regulatory Model (AERMOD) and childhood blood lead levels (BLL) in the Detroit Metropolitan Area (DMA) 2006–2013. Linear and mediation interaction regression models estimated the effects of older housing and airborne and depositional lead emission concentrations on black and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…Moody and Grady modeled airborne Pb in the Detroit Metropolitan Area using the U.S. EPA’s AERMOD model and found depositional and airborne Pb contributed directly and significantly to children’s BLLs, even after controlling for housing age and social structures, with black children at a continued disadvantage. 44 This was consistent with the authors’ prior finding that Pb-emitting facilities were primarily located in, and moving to, highly Black segregated neighborhoods regardless of poverty levels. 45 Egan et al., in their review of national survey data on BLLs collected over four decades, concluded that non-Hispanic Black race/ethnicity and poverty are consistently associated with higher BLLs.…”
Section: Discussionsupporting
confidence: 88%
“…Moody and Grady modeled airborne Pb in the Detroit Metropolitan Area using the U.S. EPA’s AERMOD model and found depositional and airborne Pb contributed directly and significantly to children’s BLLs, even after controlling for housing age and social structures, with black children at a continued disadvantage. 44 This was consistent with the authors’ prior finding that Pb-emitting facilities were primarily located in, and moving to, highly Black segregated neighborhoods regardless of poverty levels. 45 Egan et al., in their review of national survey data on BLLs collected over four decades, concluded that non-Hispanic Black race/ethnicity and poverty are consistently associated with higher BLLs.…”
Section: Discussionsupporting
confidence: 88%
“…Examples include stratifying the overall model evaluating the association between moving to a greener neighborhood and change in physical activity by area-based income [ 152 ], or as Buck Louis et al [ 153 ] included, an interaction term between birthing person race/ethnicity and chemical plasma concentration in a model testing the main effect between chemical concentration and neonatal anthropometric measurements. Authors rarely used qualitative ( n = 4 [2%] [ 41 , 57 , 65 , 154 ]) or mediation ( n = 1 [< 1%] [ 64 ]) methods.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… 68 Over the 2010s, the proportion of children in Detroit with an elevated blood lead level, defined as >5 μg/dL, was consistently around twice as high as the Michigan state-wide proportion. 69 Neighborhood-level factors associated with elevated blood lead levels among children in the Detroit area include nearby housing demolitions, 70 lead concentrations in soil, 71 depositional and airborne lead pollution from industry, 72 and older housing stock. 72 These exposure sources are disproportionately concentrated in racially-segregated (predominantly Black) Detroit neighborhoods, 72 , 73 contributing to environmental injustice among community members of all ages.…”
Section: Discussionmentioning
confidence: 99%